Frailty and poor functional status are common in arterial vascular surgical patients and affect postoperative outcomes. (June 2015) - Partridge, Judith S.L.; Fuller, Matthew; Harari, Danielle; Taylor, Peter R.; Martin, Finbarr C.; Dhesi, Jugdeep K.
Abstract: Objectives: Increasing numbers of older people are undergoing emergency and elective arterial vascular procedures. Many older patients are frail which is a recognised predictor of adverse postoperative outcomes in other surgical specialties. This study in older patients undergoing arterial vascular surgery examined; the prevalence of preoperative frailty; the clinical feasibility of preoperatively measuring frailty and functional status; the association between these characteristics and adverse postoperative outcome. Methods: Prospective observational study in patients aged over 60 years undergoing elective and emergency arterial vascular surgery. Baseline measures of frailty (Edmonton Frail Scale), functional status (gait velocity, timed up and go, hand grip strength) and cognitive function (Montreal Cognitive Assessment) were obtained preoperatively. The primary outcome measure Length of Stay (LOS) and secondary outcome measures of postoperative morbidity (medical and surgical complications), functional status and postoperative in-hospital mortality were recorded. Results: 125 patients were recruited. Frailty was common in this older surgical population (52% EFS score of ≥6.5) with high frailty scores observed (mean EFS 6.6, SD 3.05) and poor functional status (60% had TUG >15 s, 45% had gait velocity of <0.6 m/s). Higher preoperative EFS (>6.5) was univariately associated with longer LOS (≥12 days), composite measures of postoperative infections, postoperative medical complications and adverse functional outcomes. EFS≥6.5 was predictive of LOS≥12 days, adjusted for age (AUC 0.660, CI 0.541–0.779, p = 0.010). This association between EFS ≥ 6.5 and LOS ≥ 12 days was strengthened with the addition of MoCA < 24 (AUC 0.695, CI 0.584–0.806, p = 0.002). Conclusions: Patients aged over 60 years admitted for arterial vascular surgery were frail, had impaired functional status and were cognitively impaired. This combination of preoperative characteristics was predictive of longer hospital length of stay and associated with adverse postoperative outcome. Highlights: Frailty is common in older patients undergoing arterial vascular surgery. The Edmonton Frail Scale (EFS) was a feasible tool for the preoperative assessment of frailty. The EFS in older vascular surgical patients was high compared with other elective surgical groups. An EFS of ≥6.5 was predictive of longer length of hospital stay.